2022
DOI: 10.34312/jjec.v4i2.15338
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Strategi Process Oriented Guided Inquiry Learning (POGIL) Terhadap Kemampuan Proses Sains dan Literasi Kimia

Abstract: Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian quasy eksperiment desain dan menggunakan rancangan nonequivalent control group design. Populasi penelitian ini siswa kelas X SMA Negeri 3 Putra Bangsa dan sampel penelitian terdiri dari dua kelas yaitu X IPA 1 sebagai kelas eksperimen dengan jumlah 25 siswa dan kelas X IPA 2 sebanyak 25 siswa sebagai kelas kontrol. Teknik pengambilan sampel dengan menggunakan purposive sampling yaitu teknik pengambilan sampel dengan pertimbangan tertentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The average score of students' scientific literacy skills in the class taught by the POGIL model was higher than in the control class. The results of this study are in line with research results that state that the use of the POGIL model in teaching and learning activities has a positive influence on students' scientific literacy skills (Devitri & Djamas, 2019;Mellyzar et al, 2022;Nikmah & Ellianawati, 2019;Volz, 2019). Based on the output of Test Statistics, it is known that the Asymp value.…”
Section: Influence Of the Pogil Model On Students' Science Literacy A...supporting
confidence: 87%
“…The average score of students' scientific literacy skills in the class taught by the POGIL model was higher than in the control class. The results of this study are in line with research results that state that the use of the POGIL model in teaching and learning activities has a positive influence on students' scientific literacy skills (Devitri & Djamas, 2019;Mellyzar et al, 2022;Nikmah & Ellianawati, 2019;Volz, 2019). Based on the output of Test Statistics, it is known that the Asymp value.…”
Section: Influence Of the Pogil Model On Students' Science Literacy A...supporting
confidence: 87%
“…One learning model that effectively incorporates Science Process Skills is the POGIL model. Extensive research, including that by [16], demonstrates that the POGIL strategy enhances students' chemical literacy and science process skills, particularly on topics such as chemical bonding. Similarly, [15] found that POGIL plays a significant role in empowering science process skills.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the reduction of misconceptions uses cognitive conflict strategies integrated with scientific literacy. Scientific literacy is a person's ability to analyze and solve scientific problems with current issues in society (Mellyzar et al, 2022). Scientific literacy is listed in each syntax or stage of a cognitive conflict strategy (Setyarini & Admoko, 2021).…”
Section: ▪ Introductionmentioning
confidence: 99%